MALDI-TOF MS Based Bacterial Antibiotics Resistance Finger Print for Diabetic Pedopathy - Sun, Haojie; Lai, Peng; Wu, Wei; Heng, Hao; Si, Shanwen; Ye, Yan; Li, Jiayi; Lyu, Hehe; Zou, Caiyan; Guo, Mengzhe; Wang, Yu; Geng, Houfa; et al. (Frontiers in Chemistry, 2022)
Diabetes mellitus has already become the most popular global health problem. Antibiotics were still the best foundational strategy to control diabetci foot infection. Due to the lack of accurate identification of the pathogens, antibiotics were used empirically at the early stage. This non-targeted treatment not only has poor curative effect, but also minght leads to bacterial drug resistance. Therefore, timely identification of bacteria and drug resistance is the key to the treatment of diabetic foot infection. The traditional method is based on the bacterial morphology, cell physiology and biochemistry. Although the method is simple, easy to operate and with a low price, however, the clinical value is limited due to the low positive rate and long time-consuming, which delays early diagnosis and treatment. MALDI-TOF MS is one of the most representative new technologies in the field of clinical microbial identification in recent years. In this work, we have developed a strategy for the identification of drug resistance in the diagnosis of diabetic foot. Macro-proteomics and MALDI MS analysis were combined in this strategy. From the macro-proteomics result, the differential proteins which in the resistance group were obtained and the correspondence peptide fragments were used as the finger print in MALDI MS analysis. Then this strategy was successfully used in the drug resistance research in diabetic foot patients and achieved several biomarkers as finger print for 4 drugs, including ceftazidime, piperacillin, levofloxacin, and tetracycline. This method can quickly confirm the drug resistance of diabetic foot in clinical, which can help the treatment of patients as early as possible.